HISTOPATHOLOGICAL CHANGES IN GILL, KIDNEY AND LIVER OF AN ESTUA E MULLET, LIZA PARSIA, INDUCED BY SUBLETHAL EXPOSURE TO DDT - PANDEY, A. K.; SHYAMLAL, SHYAMLAL; MOHAMED, M. PEER; GEORGE, K. C. (Journal of Indian Fisheries Association, 2015)
Liza parsia were exposed to sublethal (0.02 ppm) concentration of DDT for 15 days. The gillresponded initially with copious secretion of mucus, oedematous separation of epithelial cellsfrom the basement membrane and fusion of secondary gill lamellae. Hyperplasia of the cellslining primary gill lamellae and lamellar telangiectases (or aneurysms) were frequently seenafter day 10 of exposure. Kidney exhibited hypertrophy of the epithelial cells lining proximalconvoluted tubules which was followed by shrinkage in glomerular tufts, increase in Bowman'sspace, appearance of amorphous eosinophilic materials in the lumina of the tubules and focalnecrosis on day 10 of the treatment. Hyaline droplets and casts were also encountered in theepithelial cells and lumina of the proximal tubules. Liver revealed an intitial dilation ofcanaliculi and increased secretion of bile. Thereafter, the displacement of nuclei towardsperiphery of the hepatocytes, disorganization of blood sinusoids, pyknotic changes in nuclei,cytolysis and vacuolation as well as focal necrosis were noticed after day 10 of the intoxication.